Miroku Bosatsu (Estudos Japoneses, 2010)
It is assumed that Miroku Bosatsu, Maitreya，was one of the Buddhist entities that first entered Japan and this fact raises curiosity about the origins of Japanese history and the mystique surrounding the belief in Miroku.